From Resolution until Social Religious Movement: Effort Eradication of Gambling Activity in Indonesia 1960s-1993 - Mawardi Purbo Sanjoyo, (Journal of Islamic History and Manuscript, 2023)
Gambling activity is one of the stories in the dynamics history of Indonesia. Its history can be traced from colonial to post-colonial times. In more contemporary times, gambling has even become a kind of commodity that is taken advantage of to cover the shortage of government funds. This habit became a polemic when gambling became a "disease" that was dangerous for society. To overcome this, various community groups are trying to eradicate gambling activities. Several questions were formulated, including: How did the emergence of gambling in Indonesia, its use, and the consequences? What was the process of eradicating gambling in Indonesia from the Soekarno government until the New Order government? Meanwhile, the research method used was a historical research method. The result of this study is that the process of eradicating gambling does not appear instantly. From the 1950s to the 1960s, it was filled with resolutions from social organizations. These resolutions apparently could not produce satisfactory results. In fact, in the following period, the government used gambling as an alternative economic source by imposing a tax on gambling. The struggle to eradicate gambling gained momentum in the 1990s when Muslims politically became the main consideration for the authorities at that time. The result of the movement was able to force the government to stop gambling nationally in 1993.